RUANG BUDAYA PASAR TERNAK TRADISIONAL GANG LEUMO DI KABUPATEN BIREUEN, ACEH - Aulia, Faizul; Kamil, Ade Ikhsan; Fasya, Teuku Kemal; Mursyidin, Mursyidin (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
This article investigates the cultural pursuits of the local populace within the traditional Geurugok livestock market located in the Bireuen District of Aceh. The customary markets, at the very least, depict the communal engagements within the adjacent social sphere. Diverse social exchanges can foster relationships among community members during their time at the market. Through the utilization of the Ethnophotography approach, visual imagery is employed as a data source, categorized, and scrutinized to extract culturally significant meanings aligned with the contextual aspects of space and time. The findings of this study have yielded favorable outcomes, as the depiction of the cultural significance of the community's activities within the traditional livestock markets has highlighted the systematic arrangement of these activities. This interconnection is intertwined with the market's physical layout, which offers spatial and temporal patterns for the activities undertaken, ultimately forging a cultural environment that profoundly influences their lived experiences